2022
DOI: 10.3390/children9020197
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Power Topography in Children with Attention Deficit Hyperactivity Disorder (ADHD)

Abstract: Objective: Recent years saw an increasing interest towards sleep microstructure abnormalities in attention-deficit/hyperactivity disorder (ADHD). However, the existing literature on sleep electroencephalographic (EEG) power in ADHD is still controversial, often based on single electrode recordings, and mainly focused on slow wave activity (SWA) during NREM sleep. This study aimed to systematically investigate sleep power topography in all traditional frequency bands, in all sleep stages and across sleep cycles… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…With respect to spectrum power differences, most studies focus on slow wave activity (SWA; EEG power in the 0.75–4.5 Hz band) in NREM sleep, as this parameter has a crucial role in synaptic homeostasis 15 , plasticity 16 and memory consolidation 17 . Previous studies—using high density EEG—observed higher levels of SWA in NREM sleep in ADHD children in the centro-posterial scalp derivation 18 20 . Yet, another study reported reduced SWA across the scalp in children and adolescents with ADHD compared to controls 11 .…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…With respect to spectrum power differences, most studies focus on slow wave activity (SWA; EEG power in the 0.75–4.5 Hz band) in NREM sleep, as this parameter has a crucial role in synaptic homeostasis 15 , plasticity 16 and memory consolidation 17 . Previous studies—using high density EEG—observed higher levels of SWA in NREM sleep in ADHD children in the centro-posterial scalp derivation 18 20 . Yet, another study reported reduced SWA across the scalp in children and adolescents with ADHD compared to controls 11 .…”
Section: Introductionmentioning
confidence: 85%
“…For instance, in our previous study, we found that SWA was not only associated with age, but with dogs’ weight as well; larger-sized dogs had more SWA than smaller-sized ones (for more details, see 51 ). In addition, most recent studies mapped different topographical features in ADHD children, using high-resolution EEG method 18 , 20 . In dogs’ sleep EEG studies, four EEG channels are applied (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In ADHD, sleep difficulties have been mostly viewed as an epiphenomenon of an underlying maturational disorder [ 52 , 53 , 54 , 55 , 56 ]. The role of sleep in ADHD has been mainly studied in terms of quality and continuity of sleep [ 19 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an association between externalizing behavior and deep sleep in ASD may be unlikely as well. Plausibly, these relationships may be more apparent with the use of high-density EEG and topographic mapping of SWA as shown in recent ADHD research [ 49 ].…”
Section: Discussionmentioning
confidence: 99%